Kajian Hukum Prospek Kepariwisataan Kabupaten Magetan Pada Masa Pandemi Covid-19 Terhadap Peningkatan Pendapatan Asli Daerah - Yuni Purwati; Anik Tri Haryani; Sigit Sapto Nugroho; Farah Dina Sheilawati (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
Abstract— The purpose of this study is to determine the impact of a pandemic Covid-19 to the tourism sector in the Regency of Magetan and find out the policy of the Regional Government of Kabupaten Magetan on prospects of tourism in the pandemic Covid-19. This study is a juridical empirical using qualitative analysis quantitative of data and facts in the field and supported by the approach of the legislation. The results of the study showed that the impact of a pandemic Covid-19 to the tourism sector is very visible and extraordinary, the impact negatif what happened to the tourism sector in the pandemic Covid-19, one of which is a decrease in revenue from the tourism sector this impact suffered by the offender or the Government of Kabupaten Magetan because the tourism sector is one of the post in order to increase revenue, in addition clear intensity of tourists drastically reduced. While the policy undertaken by the Government of Magetan Regency on the prospects of tourism is to make a policy better specialized programs, and also to make a decree which regulates in general related to the new life in the pandemic Covid-19 that governs related policies and things that need. Keywords—: Tourism; Pandemic Covid-19; Impact; policy.